Increased level of DNA damage in some organs of obese Zucker rats by γ‐H2AX analysis. (17th July 2017) - Azzarà, Alessia; Chiaramonte, Anna; Filomeni, Erika; Pinto, Barbara; Mazzoni, Stefano; Piaggi, Simona; Angela Guzzardi, Maria; Bruschi, Fabrizio; Iozzo, Patricia; Scarpato, Roberto
Abstract : In a recent study, we showed that lymphocytes of obese Italian children/adolescents displayed levels of double strand breaks (DSB), assayed as serine 139‐phosphorylated histone H2AX (γ‐H2AX), about eightfold higher than normal weight controls, and that 30% of this damage‐generated micronuclei. These findings suggested that obese children could be at increased risk of obesity‐mediated cancer later in life. We therefore aimed to assess the level of γ‐H2AX in a genetic animal model of obesity (Zucker rat) to identify a genotoxic/carcinogenic risk in some organs. The DSB marker was studied in 3‐ to 4‐week‐old rats and in 9‐ to 13‐week‐old rats. Paraffin‐embedded sections of heart, thyroid, liver, pancreas, lung, kidney, esophagus, and gut from the fa−/fa− (obese) and the fa+/fa− (lean) control animals were processed for immunohistochemistry detection of γ‐H2AX. Pancreas (0.0624 ± 0.0195), lung (0.1197 ± 0.0217), esophagus (0.1230 ± 0.0351), kidney (0.1546 ± 0.0149), and gut (0.1724 ± 0.0352) of 9‐ to 13‐week‐old obese rats showed a higher proportion of γ‐H2AX‐positive nuclei, than their lean counterparts (0.0092 ± 0.0033, 0.0416 ± 0.0185, 0.0368 ± 0.0088, 0.0686 ± 0.0318, and 0.0703 ± 0.0239, respectively). No difference was seen in the 3‐ to 4‐week‐old age group with regard to obesity, indicating that the DNA damage increased with older age of the rats. We hypothesize that the organs of the obese animals showing high levels of DSB could represent target tissues for the development of obesity‐related cancers. Environ. Mol. Mutagen. 58:477–484, 2017. © 2017 Wiley Periodicals, Inc.